Crucible of the Civil War : Virginia from secession to commemoration - Ayers, Edward L., 1953-; Gallagher, Gary W.; Torget, Andrew J., 1978- (Book collections on Project MUSE., 2006)
Serving both as home to the Confederacy's capital, Richmond, and as the war's primary battlefield, Virginia held a unique place in the American Civil War, while also witnessing the privations and hardships that marked life in all corners of the Confederacy. Yet despite an overwhelming literature on the battles that raged across the state and the armies and military leaders involved, few works have examined Virginia as a distinctive region during the conflict. In Crucible of the Civil War: Virginia from Secession to Commemoration, Edward L. Ayers, Gary W. Gallagher, and Andrew J. Torget, together with other scholars, offer an illuminating portrait of the state's wartime economic, political, and social institutions. Weighing in on contentious issues within established scholarship while also breaking ground in areas long neglected by scholars, several of the essays examine such concerns as the war's effect on slavery in the state, the wartime intersection of race and religion, and the development of Confederate social networks. Other contributions shed light on topics long disputed by historians, such as Virgina's decision to secede from the Union, the development of Confederate nationalism, and how Virginians chose to remember the war after its close. For anyone interested in Virginia during the Civil War, this book offers new ways to approach the study of the most important state in the Confederacy during the bloodiest war in American history.